Humic acids from an Arctic fjord, Krossfjorden, Spitsbergen - Shaji, Aswathy; Gopinath, Anu; Krishnan, Anoop; Prabhakaran, Sabu (Polish Polar Research, 2022)
Humic substances are ubiquitous materials found in terrestrial and aquatic ecosystems. Humic acids, a diagenetic product can interact with various components present in aquatic sediments. The present research is on the evaluation of sedimentary humic acids from the Krossfjorden glacial fjord situated within the Svalbard archipelago. The results of this study are needed to understand the structural characteristics of humic acids isolated from the fjord. Surface sediment samples were collected from four stations throughout the fjord during a summer period in 2018. Various spectroscopic techniques such as UV-visible, Fourier-transform infrared spectroscopy (FTIR), and Nuclear magnetic resonance spectroscopy (NMR) were applied for studying the humic acids. The elemental composition as well as the presence of tannin and lignin were also analyzed. The results of this study revealed the variation in the structure of humic acids from aliphatic to aromatic from the outer to the inner region of the fjord. This change in humic acids was well supported by the FTIR and NMR results with differences in the spectrums.